Attractive points and convergence theorems for normally generalized hybrid mappings in CAT(0) spaces - A. Kaewkhao (2018)
© 2015, Kaewkhao et al. We prove △-convergence theorems of Mann type to the set of attractive points of normally generalized hybrid mappings in CAT(0)$\operatorname {CAT}(0)$ spaces. Consequently, our main result can be applied to the result of Takahashi, Wong and Yao (Journal of Nonlinear and Convex Analysis 15:1087-1103, 2014, Theorem 5.1).